To Access the Clinical Outcomes at Three Months amongst Patients Presenting with Acute De-Compensated Heart Failure - Shahid Hussain Memon, Iftikhar Ahmed, Irfan Ali Arbab, Muhammad Hassan Butt, Javed Khurshed Shaikh, Syed Ahsan Raza, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the 3-month clinical outcome in patients with acute decompensated heart failure (ADHF). Study Design: A cross-sectional descriptive study. Place and Duration: This study was conducted at Cardiology department of Liaquat University of Medical and Health Sciences Jamshoro for six-months duration from July 2021 to December 2021. Methodology: Patients with acute de-compensated heart failure (ADHF) were involved and followed for the consequences in the form of worsening functional class, re-admission and mortality. The exercise test was performed according to the modified Bruce protocol on treadmill, with incessant on-line respiratory gas. The slope of the association between CO2 production (VCO) ventilation (VE) was evaluated by computer graphical analysis (VE / VCO2 slope). Results: 79(54.1%) of 146 patients were male. Patients' age ranged from 15 to 85 years, and the mean age was 52.10 ± 19.54 years. The patients were alienated into four age groups. Overall, 94(64.4%) of patients showed adverse clinical outcomes at three months of follow-up. Overall readmission rates were 16.7% higher in patients 51-70 years of age. Deterioration in the functional class occurred in 32.9%, less frequently in 14.6% of patients in 71-85 years of age. Mortality was found in 16.4% of patients and 37.5% of patients aged 71-90 years in the three-month follow-up. Conclusions: During the three-month follow-up period, readmissions for acute decompensated heart failure were significantly higher at a younger age, while functional class deterioration and mortality were higher at an older age.